The Transmission of Education across Generations: Evidence from Australia - Ranasinghe, Rasika (My University, 2015)
This study analyzes changes in the transmission of education across generations in Australia for the birth cohorts 1942 through 1991 using a range of measures: the estimated effect of parental education on that of the child, schooling correlations between parents and children and a series of mobility indices. Our results suggest that while the overall level of education and intergenerational education mobility has increased over time, there are considerable regional and gender differences. Daughters’ education attainment is still relatively highly correlated with their parents compared to sons and the extent of absolute upward mobility was modest while immobility and downward mobility have remained relatively steady during the last five decades. During this period, relative education opportunities have increased over time at lower education levels, while the trend has been comparatively stable at higher levels.
Keywords: Education and Training; Learning, education and training; Education and Training; Learning, education and training